Overuse Knee Pain in the Pediatric and Adolescent Athlete. Issue 11 (November 2020) - Sweeney, Emily; Rodenberg, Richard; MacDonald, James
Abstract : Abstract: Overuse knee pain is common in young athletes. There are many potential overuse injuries which present with insidious onset of pain that can challenge sports medicine providers, including Osgood-Schlatter's disease, patellofemoral syndrome, osteochondritis dissecans, and stress fractures. The differential diagnosis of insidious onset knee pain also includes malignancies, infections, and rheumatologic issues. A thorough history and physical examination can guide the treating provider in making a diagnosis and appropriate treatment plan. Although not always necessary, imaging is often helpful in overuse knee pain, and laboratory workup may be necessary. Conservative treatment is often the first recommendation in the management of overuse knee pain in young athletes, and this may include activity modification, ice, anti-inflammatory medications, bracing, and physical therapy. This review summarizes common overuse knee injuries seen in pediatric and adolescent athletes.